Preclinical Characterization of GS-9669, a Thumb Site II Inhibitor of the Hepatitis C Virus NS5B Polymerase - Fenaux, Martijn (American Society for Microbiology, 2013)
GS-9669 is a highly optimized thumb site II nonnucleoside inhibitor of the hepatitis C virus (HCV) RNA polymerase, with a binding affinity of 1.35 nM for the genotype (GT) 1b protein. It is a selective inhibitor of HCV RNA replication, with a mean 50% effective concentration (EC(50)) of ≤11 nM in genotype 1 and 5 replicon assays, but lacks useful activity against genotypes 2 to 4. The M423T mutation is readily generated clinically upon monotherapy with the thumb site II inhibitors filibuvir and lomibuvir, and it is notable that GS-9669 exhibited only a 3-fold loss in potency against this variant in the genotype 1b replicon. Rather than M423T, resistance predominantly tracks to residues R422K and L419M and residue I482L in GT 1b and 1a replicons, respectively. GS-9669 exhibited at least additive activity in combination with agents encompassing four other direct modes of action (NS3 protease, NS5A, NS5B via an alternative allosteric binding site, and NS5B nucleotide) as well as with alpha interferon or ribavirin in replicon assays. It exhibited high metabolic stability in in vitro human liver microsomal assays, which, in combination with its pharmacokinetic profiles in rat, dog, and two monkey species, is predictive of good human pharmacokinetics. GS-9669 is well suited for combination with other orally active, direct-acting antiviral agents in the treatment of genotype 1 chronic HCV infection. (This study has been registered at ClinicalTrials.gov under registration number NCT01431898.)